Central Role of Relatedness in Alaska Native Youth Resilience: Preliminary Themes from One Site of the Circumpolar Indigenous Pathways to Adulthood (CIPA) Study. Issue 3 (3rd October 2013) - Wexler, Lisa; Moses, Joshua; Hopper, Kim; Joule, Linda; Garoutte, Joseph; ,
Abstract: This qualitative study of youth resilience takes place in an Alaska Native community, which has undergone rapid, imposed social change over the last three generations. Elders, and successive generations have grown up in strikingly different social, economic and political contexts. Youth narratives of relationships in the context of adolescent growth and development offer insights to better understand culturally‐patterned experience, continuity and change. Local youth and adults shaped the design, implementation and analysis phases of this participatory study. Multiple interviews, totaling 20 older (ages 15–18) and younger (11–14) boys and girls provide accounts of everyday lives and life histories. Although losing close relationships was the most common stressor, many of the participants' resilience strategies centered on their connections to others. Participants cultivated 'relatedness', nurturing relationships that took on kinship qualities. Within these relationships, youth participants acted more responsibly and/or developed a sense of competency and self‐worth because of others' reliance on them.